Family Relationships Under Work From Home: Exploring the Role of Adaptive Processes - Wu, Hongyue; Song, Q. Chelsea; Proctor, Robert W.; Chen, Yunfeng (Frontiers in Public Health, 2022)
Work-from-home (WFH) influences both work and life, and further impacts family relationships. The current study explores the impacts of WFH on family relationships during the COVID-19 pandemic and identifies effective adaptive processes for maintaining family relationships under WFH. Using the Vulnerability-Stress-Adaptation (VSA) model, the study examines the roles of adaptive processes (spending time with family members and balancing work and life) and demographic differences (gender, age, marital status, and education level) in the relation between WFH and family relationships. Path analysis results based on an online survey (N=150) suggested that, overall, WFH improved family relationships through proper adaptive processes. WFH had a positive relation to time spent with family members, and this relation was especially salient for workers with lower education levels. While there was no significant overall relation between WFH and work-life balance, older workers tended to engage in increased work-life balance during WFH. Both adaptive processes were positively related to family relationship quality. The findings advance the understanding of family relationships and WFH, and the study provides practical recommendations to enhance family relationships under WFH.